ENCOURAGING PARTICIPATION IN ONLINE DISCUSSION FORUMS WITH UNIVERSITY EFL LEARNERS - Rodríguez-Juárez, Carolina; Oxbrow, Gina (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Using an e-learning environment undoubtedly has many advantages in foreign language learning contexts, especially when we consider their potential for enhancing learner autonomy and providing out-of-class language practice as well as maintaining language learning motivation. In this paper we describe an action research project conducted with first-year university students enrolled in the degree “English Language and Literature” (“Filología Inglesa”) at the University of Las Palmas de Gran Canaria in the Canary Islands, Spain, which explores affective and methodological reasons for limited participation in our interactive online learning platform (“Moodle”). We report on the effect of using different formats in the discussion forum application in our virtual learning environment (“Campus Virtual”) and the insights for future practice that we have gained. Resumen La utilización de un entorno virtual de aprendizaje tiene, sin duda, muchas ventajas en contextos de aprendizaje de segundas lenguas, sobre todo en relación con su potencial para fomentar la autonomía del alumno y ofrecer práctica suplementaria fuera del aula, así como para mantener la motivación. En este artículo describimos un proyecto de investigación acción llevado a cabo con alumnos universitarios de primer curso matriculados en la asignatura de “Lengua Inglesa I” impartida en la licenciatura “Filología Inglesa” en la Universidad de Las Palmas de Gran Canaria, Islas Canarias, España, que analiza razones afectivas y metodológicas para explicar la participación limitada en nuestra plataforma virtual (“Moodle”). Presentamos los resultados del proyecto en relación con el efecto de la utilización de distintos formatos de foros de discusión en nuestro Campus Virtual así como datos reveladores que pretendemos incorporar en nuestra práctica docente.